Theoretical approaches to the management of industries - Nakipova, G.N.; Arynova, Zh.Z. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the actual problem of building economic systems of new quality in society, namely in the food sector. The authors reveal the tasks, forms and types of economic systems of new quality in the food sector. The authors focus on the use of such approaches as: revolutionary, evolutionary, systemic, factorial, target, and factor-targeted. They give a comparative description of each approach, taking into account its features. Using a systematic integrated approach, an author’s vision of the functioning of the food sector, which is shown in the form of a diagram, is given. As a result of the analysis of the economic literature, the authors synthesize its results, highlighting the main stages and characteristics of the use of revolutionary approaches in the transformation of economic systems. Particular attention is drawn to the holistic view of the studied theoretical approaches to the management of the food sector. The study of the factor approach allowed us to identify its main components and determine their properties. The model of factor analysis is considered in detail, its distinctive characteristics and influence on the activity of the food sector. It should be noted that the authors conducted a rather detailed assessment of the program-target approach as the most common in practice of managing sectors of the economy. Following the results of a comprehensive study of theoretical approaches to the management of economic sectors, the authors came to the conclusion that the factor-target approach is the most effective in the context of modernizing the food sector.